Psychological Study of the behavior standards in traffic environments, in groups of private and professional drivers in Lima - Ponce D., Carlos (2006)
Objectives: 1. To understand behaviour styles of private and public service drivers in Lima, Metropolitan Area. 2. To detect the existence of significant differences in behaviour styles in traffic environments, within private and public service drivers of Lima, Metropolitan Area, in a global and specific manner. 3. To investigate the existence of significant differences of behaviour styles in traffic environments, within private and public service drivers of Lima, Metropolitan Area, in relation to the following variables: age, civil status, education level, geographical origin, vehicle property, driving as a main occupation, driving schedule/time length, traffic accidents record, traffic tickets, health problems, hearing problems, motor faculties, family problems and emotional problems. 4. To study the reliability and validity of the PSS questionnaire that evaluates behavior patterns of driver in traffic environments.